Baccharis ibitipocensis (Asteraceae: Astereae) a new species endemic from Serra de Ibitipoca, Minas Gerais, Brazil - Deble, Leonardo Paz (Balduinia, 2014)
Baccharis ibitipocensis, a new species of section Oblongifoliae DC. is described and illustrated. Comments about the new taxa and related species are also furnished.